Sustainable Biodiesel Production from Waste Cooking Oil Using Diatomite as a Catalyst - Md Huzir, Nurhamieza; Amin, Azlan Nur Rasyid; Tamunaidu, Pramila; Vadivelu, Yogeswary (International Journal of Integrated Engineering, 2025)
Biodiesel production from waste cooking oil via the transesterification process is one of the sustainable alternatives to fossil fuels. This study explores single use of diatomite as an alternative catalyst for biodiesel production that can significantly benefit the green energy industry. The experiment manipulated the methanol-to-oil ratio and catalyst dosage required by transesterification of fresh and waste cooking oil to maximize biodiesel yield. The use of diatomite in the transesterification of waste cooking oil produced a biodiesel yield of 90.49%, which was closely comparable to the 93.28% yield obtained from fresh cooking oil. The optimal condition was achieved with a 6:1 molar ratio of methanol to oil and 1.0 wt% diatomite. FTIR analysis of biodiesel sample from fresh and waste cooking oil produce new peaks at 1435 cm⁻¹ attributed to methyl bending vibration that occurs in alkanes which reflects characteristic of the biodiesel composition. In addition, presence of methyl ester was confirmed at 1196 cm⁻¹ which verified succesful of transesterification process. Diatomite's reusability was efficient, achieving up to 70% conversion after three cycles, showing its potential to reduce biodiesel production costs. This study demonstrated that diatomite was an effective catalyst for the transesterification process, contributing to the advancement of sustainable biodiesel energy.